Navigating Social Phobia And Emotional Regulation In Patients Afflicted By Psychogenic Non-Epileptic Seizures (PNES) And Temporal Lobe Epilepsy: An In-Depth Exploration - Badawy, Dr. Walaa Badawy Mohamed (Migration Letters, 2024)
The aim of this research was to explore the link between social anxiety and the challenge of managing emotions in individuals diagnosed with psychogenic non-epileptic seizures (PNES) and temporal lobe epilepsy (TLE), employing the State Social Phobia Questionnaire (SSAQ) and the State Emotional Regulation Questionnaire (SERQ). This approach to screening had not previously been applied to such patient groups. The study comprised fifty participants, whose inclusion was based on a review of their medical records, diagnoses, and EEG results. These individuals were recruited from the Psychiatry and Neurology Department of the School of Medicine at Menoufia University. The average age of the participants was 31.8, with a standard deviation of 10.66, among the total group (n=50), divided between 22 individuals with TLE and 28 with PNES, with their ages ranging from 18 to 50. Additional psychological assessments were conducted to confirm and address the issues identified. The participants completed questionnaires that collected demographic information and responses to items from both assessment tools. Analysis using Pearson’s method identified a moderately significant relationship (r = 0.528) between those with PNES and TLE patients (r = 0.754). Likewise, a positive relationship was observed between social anxiety and emotion regulation among both groups, indicating that psychological and social factors are more closely linked to the control of emotions rather than a lack of such control.